Dispositional Gratitude Moderates the Association between Socioeconomic Status and Interleukin-6 - Andree Hartanto (Nature Portfolio, 2019)
Abstract Socioeconomic disparities in health are prevalent and growing in importance as a concern among academics, policymakers, and the general public. However, psychological resources that can narrow such disparities have not been well-examined. The current study examined the moderating role of dispositional gratitude in the relationship between socioeconomic status (SES) and inflammation risk as an index of health. Participants consisted of 1,054 midlife adults from the biomarker project of the Midlife in the United States. Inflammation risk was measured by interleukin-6 biomarker and SES was operationalized by education attainment and income. We found that dispositional gratitude significantly moderated the relationships between SES and interleukin-6. Among individuals with low dispositional gratitude, higher SES was significantly associated with lower levels of interleukin-6. However, the association between SES and interleukin-6 was not significant among individuals with high dispositional gratitude. More importantly, the findings remained robust after controlling for demographic characteristics, health status, health behaviours, and personality traits. Our findings suggest that gratitude may serve as an important psychological resource in attenuating health-related risk from socioeconomic stressors.